Indigenous knowledge as solution to the unmet need for contraceptives - Matlala, S. F. (CALABASH: Indigenous Studies Journal, 2009)
At the 1994 International Conference on Population and Development (ICPD) held in Egypt and at the subsequent conference to review progress held in 1999, one of the goals set was a universal access by 2015 to the widest possible range of safe and effective family planning methods by men and women of reproductive age. The other more challenging goal set at ICPD was elimination of the unmet need for family planning by 2015. Millions of unintended pregnancies still occur all over the world every year while millions more other couples are willing to use family planning but lack access to safe, effective and acceptable methods. This challenge is a result of increased number of family planning users due to success of family planning campaigns, increased number of people of reproductive age and a marked decline in available funding for reproductive health services experienced by most developing countries. This paper argues that indigenous contraceptives can be used to meet this unmet need.
Journal article
Keywords: Indigenous knowledge; Indigenous contraceptives; Birth control; Contraceptives; Indigenous peoples